Myoelectric grip force prediction using deep learning for hand robot - Anam, Khairul; Ardhiansyah, Dheny Dwi; Hana Sasono, Muchamad Arif; Nanda Imron, Arizal Mujibtamala; Rizal, Naufal Ainur; Ramadhan, Mochamad Edoward; Muttaqin, Aris Zainul; Castellini, Claudio; Sumardi, Sumardi (Institute of Advanced Engineering and Science, 2025)
Artificial intelligence (AI) has been widely applied in the medical world. One such application is a hand-driven robot based on user intention prediction. The purpose of this research is to control the grip strength of a robot based on the user’s intention by predicting the grip strength of the user using deep learning and electromyographic signals. The grip strength of the target hand is obtained from a handgrip dynamometer paired with electromyographic signals as training data. We evaluated a convolutional neural network (CNN) with two different architectures. The input to CNN was the root mean square (RMS) and mean absolute value (MAV). The grip strength of the hand dynamometer was used as a reference value for a low-level controller for the robotic hand. The experimental results show that CNN succeeded in predicting hand grip strength and controlling grip strength with a root mean square error (RMSE) of 2.35 N using the RMS feature. A comparison with a state-of-the-art regression method also shows that a CNN can better predict the grip strength.